2021
DOI: 10.1126/science.abf9279
|View full text |Cite
|
Sign up to set email alerts
|

Babbling in a vocal learning bat resembles human infant babbling

Abstract: Babbling bats A notable aspect of language development in humans is the babbling stage. During this time, toddlers make a range of specific sounds as they practice and imitate adult speech. Humans are not the only vocal learners, however, so might we expect such babbling among others? Fernandez et al . recorded the vocalizations of sac-winged bat pups in the wild and found clear evidence of babbling that was consistent with that seen in humans. The shared babbling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
(20 reference statements)
3
37
0
Order By: Relevance
“…Thus, nestlings gradually increased their output and repertoire of call types, followed by a pruning and refining period. This is consistent with the overproduction and selective attrition model of songbird and mammalian vocal development [1,2,27,4143]. However, CORT-treated birds tended to skip the pruning (higher k ), but not the refining period (more spherical clusters, figure 2 f ) during the post-treatment period.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, nestlings gradually increased their output and repertoire of call types, followed by a pruning and refining period. This is consistent with the overproduction and selective attrition model of songbird and mammalian vocal development [1,2,27,4143]. However, CORT-treated birds tended to skip the pruning (higher k ), but not the refining period (more spherical clusters, figure 2 f ) during the post-treatment period.…”
Section: Discussionsupporting
confidence: 83%
“…Acoustic variability is reduced over vocal development in several species that learn to refine their vocalizations with experience [e.g., humans (Lee et al, 1999 ), birds (Ölveczky et al, 2011 ), and bats (Fernandez et al, 2021 )]. We found that prairie voles, a presumed vocal non-learning species, exhibited a similar pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experimental field studies that cover a few seasons can reveal fascinating insights into the behavior of wild bats. This includes studies on communication and cognition in bats (e.g., Page and Ryan 2005 ; Hernández-Montero et al 2020 ; Fernandez et al 2021 ). Finally, even field studies addressing the effect of anthropogenic changes of the environment on bats, such as the impact of light pollution on habitat use, do not always require individualized long-term data (e.g., Stone et al 2009 ).…”
Section: Why Do We Need Long-term Field Studies On Bats?mentioning
confidence: 99%
“…The greater sac-winged bat has been studied for 50 years (M. Knörnschild et al, unpublished data), which makes it one of the best studied tropical bat species. This iconic species is well-known for its fascinating mating behavior as well as complex acoustic and olfactory communication (e.g., Nagy et al 2007 , 2012 ; Fernandez et al 2021 ). However, because of population crashes in the respective study populations in Costa Rica and Panama (Nagy et al 2012 ; M. Knörnschild et al, unpubl.…”
Section: Future Perspectives Of Long-term Field Studies On Batsmentioning
confidence: 99%